Against All Odds? The Enduring Value of Liberal Education in Universities, Professions, and the Labour Market - Axelrod, Paul; Anisef, Paul; Lin, Zeng (Canadian Journal of Higher Education, 2001)
The humanities, the social sciences and the fine arts — the core subjects of liberal education — are at risk in Canadian universities, and the danger arises largely from the forced reorientation of higher education to assumed market needs. This paper attempts to explain why such policy shifts are occurring; it points to the continuing cultural, social and intellectual value of liberal education; and, drawing from recent and previously unreported census data, it demonstrates that liberal education produces generally positive economic benefits to the individual graduate. It concludes that policies designed to diminish the presence of liberal education in universities in favour of more supposedly "market-worthy" subjects are short-sighted and threatening to the integrity and vitality of higher education.